Pengaruh Harga, Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Mie Gacoan Cabang Tulungagung - Muhammad Zakki Irsyada, Zakki (CV.RIZANIA MEDIA PRATAMA, 2024)
This research is meant to find out the influence of price, promotion, and product quality on purchasing decisions. This type of research is associative research or research used to test whether there is a relationship between variables from two or more sets of data using a quantitative approach. The population of this study is customers of Mie Gacoan Branch in Tulungagung, and a sample of 120 is taken using purposive sampling method, which sets limitations such as specific characteristics or considerations. The data analysis technique in this research uses multiple linear regression analysis. The hypothesis test results of this study indicate that partially, the price variable (X1) has a positive and significant effect on purchasing decisions (Y). This can be seen from the path coefficient value of 0.006 < 0.05 and the tvalue of 2.819 > ttable value of 1.658. The promotion variable (X2) also has a positive and significant effect on purchasing decisions (Y). This is evident from the path coefficient value of 0.000 < 0.05 and the tvalue of 6.208 > ttable value of 1.658. The product quality variable (X3) has a positive and significant effect on purchasing decisions (Y). This can be seen from the path coefficient value of 0.044 < 0.05 and the tvalue of 2.032 > ttable value of 1.658. Based on the Ftest results, it shows that the calculated Fvalue is greater than the tabulated Fvalue, which is 501.705 > 2.68 with a significance value of 0.000 < 0.05. The variables price, promotion, and product quality simultaneously have a positive and significant influence on purchasing decisions at the Mie Gacoan Branch in Tulungagung. Therefore, it can be concluded that price, promotion, and product quality both partially and simultaneously have a positive and significant effect on purchasing decisions at the Mie Gacoan Branch in Tulungagung.